2018
DOI: 10.1103/physreve.97.012413
|View full text |Cite
|
Sign up to set email alerts
|

Growth-mediated autochemotactic pattern formation in self-propelling bacteria

Abstract: Bacteria, while developing a multicellular colony or biofilm, can undergo pattern formation by diverse intricate mechanisms. One such route is directional movement or chemotaxis toward or away from self-secreted or externally employed chemicals. In some bacteria, the self-produced signaling chemicals or autoinducers themselves act as chemoattractants or chemorepellents and thereby regulate the directional movements of the cells in the colony. In addition, bacteria follow a certain growth kinetics which is inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
4
17
0
Order By: Relevance
“…( In addition to the particle-based simulations, we have also numerically solved the system of the four coupled dimensionless PDEs of the continuum model, Eqs. (9,10,11) as before in two spatial dimensions with periodic boundary conditions. We use a forward Euler method to propagate the densities ρ s and the chemical fields c s in time.…”
Section: Data Availabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…( In addition to the particle-based simulations, we have also numerically solved the system of the four coupled dimensionless PDEs of the continuum model, Eqs. (9,10,11) as before in two spatial dimensions with periodic boundary conditions. We use a forward Euler method to propagate the densities ρ s and the chemical fields c s in time.…”
Section: Data Availabilitymentioning
confidence: 97%
“…It is involved in many biological processes where microorganisms (or cells) coordinate their motion; these include wound healing, fertilization, pathogenic invasion of a host, and bacterial colonization [1, 2]. In such cases, microorganisms are attracted (or repelled) by certain substances (chemoattractants/ chemorepellents), but they are also attracted to chemicals produced by other microorganisms (or cells), such as cAMP in the case of Dictyostelium cells [3] or autoinducers in signaling Escherichia coli [4], which leads to chemical interactions (communication) among the microorganisms.While many existing models studying microbiological chemotaxis (or chemical interactions) focus on a single species [5][6][7][8][9][10][11][12], the typical situation in the microbiological habitat is that various different species simultaneously produce certain chemicals to which others respond via chemotaxis or based on quorum sensing mechanisms. One simple example involving chemical signaling across species is provided by macrophage-facilitated breast cancer cell invasion which has recently been modeled [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The instability can occur either due to anisotropy in the chemical production of Janus colloids, leading to the so-called "Janus-instability", or due to memory (delay) effects which can create an oscillatory instability leading to traveling wave and traveling lattice patterns. Based on the model of [92], in [170] it has been demonstrated that repulsive phoretic interactions and a logistic growth for particle (bacteria) concentration can lead to ring and spot patterns resembling experimental observations [171].…”
Section: Methodsmentioning
confidence: 87%
“…Starting from the coherent motion of cells in tissue flow, motion in bacteria, fish, and birds, this also holds for collective migration of animals [1][2][3][4]. In micro-organisms, selfpropulsion is a form of active motion that is responsible for the emergence of various orders in cell-collectives such as motility-induced phase-separation [5], chemotaxis [6][7][8], pattern formation [9][10][11][12][13][14], swarming and turbulent motions [15][16][17][18][19][20]. Bacterial swarming is an efficient mode of collective migration of a group of densely-packed, rod-shaped flagellated bacteria on the surface.…”
Section: Introductionmentioning
confidence: 99%